Observe the roots, don't expand

Calculus Level 2

1 7 ( x 1 ) ( x 7 ) d x = ? \large \int_{\color{#20A900}1}^{\color{#3D99F6}7} (x-\color{#20A900}1)(x-\color{#3D99F6}7) \, dx = \ \color{grey}?

Bonus : Can you generalize this for A B ( x A ) ( x B ) d x \displaystyle \int_A^B (x-A)(x-B) \ dx ?


The answer is -36.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

4 solutions

Discussions for this problem are now closed

Tan Yong Boon
Dec 25, 2014

The solution to this problem is rather simple if you were to use a certain property of definite integrals:

α β ( x α ) ( x β ) d x = 1 6 ( β α ) 3 \int_\alpha^\beta (x -\alpha)(x - \beta) dx = - \frac{1}{6}(\beta-\alpha)^{3}

Here's the proof:

α β ( x α ) ( x β ) d x \int_\alpha^\beta (x - \alpha)(x- \beta) dx

= α β [ x 2 ( α + β ) x + α β ] d x = \int_\alpha^\beta [x^{2} - (\alpha + \beta)x + \alpha\beta] dx

= [ 1 3 x 3 ] α β ( α + β ) [ 1 2 x 2 ] α β + α β [ x ] α β = [\frac{1}{3}x^{3}]_\alpha^\beta - (\alpha + \beta)[\frac{1}{2}x^{2}]_\alpha^\beta + \alpha\beta[x]_\alpha^\beta

= 1 3 ( β 3 α 3 ) 1 2 ( α + β ) ( β 2 α 2 ) + α β ( β α ) = \frac{1}{3}(\beta^{3} - \alpha^{3}) - \frac{1}{2}(\alpha + \beta)(\beta^{2} - \alpha^{2}) + \alpha\beta(\beta - \alpha)

= 1 6 ( β α ) [ 2 ( β 2 + α β + α 2 ) 3 ( β + α ) 2 + 6 α β ] = \frac{1}{6}(\beta - \alpha)[2(\beta^{2} + \alpha\beta + \alpha^{2}) - 3(\beta + \alpha)^{2} + 6\alpha\beta]

= 1 6 ( β α ) ( β 2 + 2 α β α 2 ) = \frac{1}{6}(\beta - \alpha)(-\beta^{2} + 2\alpha\beta - \alpha^{2})

= 1 6 ( β α ) 3 = -\frac{1}{6}(\beta - \alpha)^{3}

As such, we have

1 7 ( x 2 8 x + 7 ) d x = 1 6 ( 7 1 ) 3 = 36 \int_1^7 (x^{2} - 8x + 7) dx = - \frac {1}{6}(7-1)^{3} = \boxed{-36}

It's just as simple to just integrate and then plug the values in; that wastes a lot of time, however. This is a quick shortcut, and a good one, at that.

tytan le nguyen - 6 years, 5 months ago

we this The solution to this problem is rather simple if you were to use a certain property of definite integrals.

Romeo Conbolt - 6 years, 5 months ago
Roy Tu
Jan 18, 2015

Slightly overengineered solution: make the substitution

x = y + 4 d x = d y 3 3 ( y + 3 ) ( y 3 ) d y 2 0 3 ( y + 3 ) ( y 3 ) d y 2 0 3 y 2 9 d y 2 ( y 3 3 9 y ) 0 3 2 ( 9 27 ) 2 ( 18 ) = 36 x = y+4 \\ dx = dy \\ \int^3_{-3}{(y+3)(y-3)} dy \\ 2\int^3_0{(y+3)(y-3)} dy \\ 2\int^3_0{y^2-9} dy \\ 2(\frac{y^3}{3}-9y)|^3_0 \\ 2(9-27) \\ 2(-18) = \boxed{-36}

Makes it a bit easier to do mentally.

The common way to calculate just to test his theory .

Tibrôncio Cavalcante - 6 years, 5 months ago
Hobart Pao
Dec 30, 2014

I did it the slow way, expand, 1 7 ( x 2 8 x + 7 ) d x \int_{1}^{7}(x^{2}-8x+7)dx , then use reverse power rule, to integrate, which produces 1 3 x 3 4 x 2 + x 7 \frac{1}{3}\cdot x^{3}-4\cdot x^{2}+x\cdot 7 . After that, substitute in 7 into the expression, and subtract the result of substituting 1 into the expression. ( 1 3 7 3 4 7 2 + 7 7 ) ( 1 3 1 3 4 1 2 + 7 1 ) \left (\frac{1}{3}\cdot 7^{3}-4\cdot 7^{2}+7\cdot 7 \right )-\left (\frac{1}{3}\cdot 1^{3}-4\cdot 1^{2}+7\cdot 1 \right ) This produces the result 36 -36

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...